A population-based study of premorbid scholastic achievement among patients with psychiatric disorders. (July 2017) - Ullman, Vardit Zerem; Hornik-Lurie, Tzipi; Reichenberg, Abraham
Abstract: Population-based studies of premorbid cognitive functioning in schizophrenia have found verbal deficits and low IQ scores. It remains unclear, however, whether premorbid deficits are specific to schizophrenia, compared with other psychiatric disorders. Moreover, studies using school-based measures are few and their results inconsistent. This study assesses the eighth-grade (ages 13–14; n=11, 418) scholastic performance of adults with psychiatric disorders (n=194, 1.7, particularly with schizophrenia (n=86, 0.8%), comparing the results with those of their normative peers. The researchers examined report cards of eighth-graders at state secular schools in Jerusalem over a ten-year period (1978–1988), applying ANOVA and logistic regression models to evaluate associations between school performance and subsequent psychiatric hospitalization. The findings indicated that participants hospitalized with varied psychiatric disorders had lower grades in mathematics, gym, handcraft and academic core subjects, with significantly lower overall scores. Amended logistic regression models indicate that reduced performance (in mathematics, gym, handcraft and overall scores) was correlated with an increasing likelihood of hospitalization for the psychiatric disorders group and the subgroup with schizophrenia-related ailments. These results imply that eighth-grade school performance in core subjects is poorer among persons later hospitalized with psychiatric disorders than that of their classmates. Highlights: We compared persons hospitalized for psychiatric disorders versus their peers. Poor school performance at age 13–14 correlates with psychiatric disorders. Persons with psychiatric disorder displayed poor performance in all core subjects. Low premorbid achievements are associated with increased risk for admissions.